Beyond Income: Modeling the Dual Role of Livelihood Training in Organic Agriculture Production in Mitigating Socio-Economic Vulnerability and Household Conflict - Campos, Josephine Diana; Campos, Jofrey (International Journal of Entrepreneurship and Sustainability Studies, 2025)
This study models the dual role of livelihood training in addressing socio-economic vulnerability and household conflict among marginalized urban populations in the Philippines. Focusing on Bagong Silang, Caloocan City—the nation’s most populous and poverty-stricken barangay—the research investigates how demographic factors such as age, marital status, and number of children shape socio-economic status, influence training preferences, and intensify domestic stressors. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) and data from 100 purposively selected respondents, the study reveals a robust structural pathway: socio-economic status mediates the relationship between demographic profiles and both livelihood choices and family-related challenges. Results show high explanatory power (R² = 0.85 for Family Challenges, 0.79 for Training Preferences, 0.76 for Socio-Economic Status), validating the interdependence of economic conditions and household dynamics. Significantly, the findings position livelihood training not merely as a tool for income generation but as a social stabilizer—especially when aligned with the lived realities of vulnerable groups such as solo parents, informal workers, and unemployed youth. Preferred training in organic agriculture, financial literacy, and responsible parenting directly alleviate family conflict and financial stress. This study advances poverty discourse by offering an evidence-based framework that integrates demographic sensitivity into community interventions. It urges policymakers and development actors to move beyond one-size-fits-all solutions and instead implement targeted, demographically informed livelihood programs that foster both economic resilience and familial well-being.